Kerentanan Perempuan dalam Pengelolaan Air Rumah Tangga Selama Pandemi COVID-19 di Jakarta Utara - Ellen Suryanegara; Herdis Herdiansyah; Donna Asteria (Jurnal Penelitian Pendidikan IPA, 2023)
Human population growth, the rapid development of urban areas, and climate change were causing a scarcity of freshwater resources. Providing water and sanitation is important to protect the health during a pandemic. However, North Jakarta still faces problems in meeting the water demands of its residents. The COVID-19 pandemic expands the challenges faced by vulnerable individuals living in poverty and without access to health services, water, sanitation, and adequate housing, especially for women. During the COVID-19 pandemic, woman's responsibilities became even heavier; aside from paying attention to their safety and health, women were often burdened with domestic roles towards their families and their responsibility for collecting water supplies for the household. This study examines the situation of women's vulnerability in household water management in the urban environment of North Jakarta, especially during the COVID-19 pandemic. A quantitative approach with descriptive statistical analysis was used in this study. The result of this study portrays women's vulnerability in household water management during the COVID-19 pandemic in North Jakarta in two categories, 49.26% have a high level of vulnerability, and 50.74% have a low level of vulnerability. The level of exposure, sensitivity, and response capacity assessed the vulnerability components. This study is expected to be a reference for sustainable water management, considering gender roles and conditions in urban environments, especially during disasters.